2019
DOI: 10.1039/c9ra03173a
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein adsorption on a titanium surface and its effect on osteoblast behaviors

Abstract: This study aims to investigate the adsorption of low density lipoprotein (LDL) on a titanium surface and to explore its effect on osteoblast behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The XPS spectra (figure 4) showed that peaks of Ti 2p and O 1s gradually declined with an increase in the concentration of SEMA4D, indicating that SEMA4D was immobilized onto the titanium surfaces, and surface oxides were covered by the complex [69]. Since protein molecules contain many functional groups, the C 1s spectra consist of different peaks [70].…”
Section: Discussionmentioning
confidence: 99%
“…The XPS spectra (figure 4) showed that peaks of Ti 2p and O 1s gradually declined with an increase in the concentration of SEMA4D, indicating that SEMA4D was immobilized onto the titanium surfaces, and surface oxides were covered by the complex [69]. Since protein molecules contain many functional groups, the C 1s spectra consist of different peaks [70].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study found a negative correlation between LDL-C and lumbar bone density in individuals aged 20–59 years [ 4 ]. Furthermore, an in vitro study demonstrated that LDL adsorption negatively regulated osteoblast behaviors, such as adhesion, proliferation and differentiation [ 5 ]. These studies suggest the need for further research into the relationship between LDL-C and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%